Online Presence System Using Geolocation and Digital Signature at the Rejang Regency Defense Office - Jana, Septi Nur (P3M Politeknik Negeri Media Kreatif, 2023)
The development of information technology has now reached all fields, both in the security sector, education sector, and office sector, as well as other aspects of human life. The need for accurate, precise and fast information in presenting very complete data is one of the important goals, for this smartphone plays an active role in all fields and will make human work easier. One of the assessments of employee performance is absenteeism. Currently there is a Finger Print-based attendance system that is running at the Rejang Lebong District Land Office, but there are still problems with attendance, where employees who are on duty outside the city/field find it difficult to attend because attendance can only be done in the office. Therefore an Online Presence System was created using Geolocation and Digital Signature at the District Land Office. Rejang Lebong as a solution to this problem. This system was created using the Rapid Application Development (RAD) method. The data analysis methods in this research are Descriptive Analysis: Summarizes the general characteristics of attendance data, Digital Signature Usage Analysis: Measuring the extent to which employees adopt and use digital signatures, Geolocation Accuracy Evaluation: Measuring the accuracy of the location provided by the system, Attendance Pattern Analysis: Knowing the pattern employee attendance, Digital Signature Security Test: Ensuring the security and integrity of the digital signature, User Satisfaction Analysis: Evaluating user satisfaction with the system, and Digital Signature and Geolocation Integration Analysis: Assessing the contribution of the integration of these two features to the success of the system. After testing, it can be confirmed that the system that has been created can work well.